Double-shell high-thermal-conductivity phase change heat storage microcapsule for ultra-deep drilling fluid as well as preparation method and application of double-shell high-thermal-conductivity phase change heat storage microcapsule

The double-shell high-thermal phase change heat storage microcapsules prepared by two-step coating method solve the problems of low phase change temperature and low thermal conductivity of phase change materials in drilling fluid, significantly lowering the drilling fluid temperature and increasing the high temperature The tolerance of the formation enhances drilling safety.

CN119193120AActive Publication Date: 2024-12-27CHINA UNIV OF PETROLEUM (EAST CHINA)

Patent Information

Application Number
CN202411317096.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2024-12-27
Estimated Expiration
2044-09-20

AI Technical Summary

Technical Problem

The phase change temperature and thermal conductivity of the phase change materials in existing drilling fluids are low, making it difficult to effectively reduce the impact of high temperatures at the ultra-deep bottom on the drilling fluid, resulting in an increased risk of safety accidents such as well wall instability and drilling.

Method used

The double-shell high-thermal phase-change heat storage microcapsules were prepared by two-step coating method. By combining the phase-change material with high phase-change temperature with the high-thermal-conducting material, a microcapsule with eutectic phase-change material as the core and inorganic shell was formed. , significantly improves the thermal conductivity and latent heat of the drilling fluid.

Benefits of technology

It significantly reduces the temperature of the drilling fluid, improves tolerance to high-temperature formations, avoids well wall instability and drilling fluid system failure, and improves drilling safety and efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to a double-shell high-thermal-conductivity phase-change heat storage microcapsule for an ultra-deep drilling fluid as well as a preparation method and application of the microcapsule, and belongs to the field of drilling fluid chemistry in the petroleum industry. According to the invention, two high-melting-point phase change materials and eutectic compounds of the two phase change materials are respectively used as core materials, the double-shell high-thermal-conductivity phase change heat storage microcapsule for the ultra-deep drilling fluid is prepared by coating an external shell layer twice, the material has a high phase change temperature, the phase change temperature is 173.3-230.7 DEG C, the phase change enthalpy is up to 211.4 J / g, and the phase change heat storage microcapsule can be used for the ultra-deep drilling fluid. When the material is in a phase change temperature range, a large amount of heat can be absorbed, the effect of phase change latent heat is achieved, and when the material is applied to drilling fluid, the temperature of the drilling fluid can be remarkably reduced, and the tolerance of the drilling fluid to high-temperature strata is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a double-shell high thermal conductivity phase change heat storage microcapsule for ultra-deep drilling fluid and a preparation method and application thereof, belonging to the field of drilling fluid chemistry in the petroleum industry. Background Art

[0002] my country is rich in deep and ultra-deep oil and gas resources, with a total resource volume of 671×10 8 Tons, of the newly discovered reserves in the past 10 years, deep and ultra-deep oil and gas resources account for more than 50%, and their efficient development is of great significance to ensuring national energy security. In the process of drilling deep and ultra-deep formations, drilling fluid plays a vital role and is the core technology for carrying cuttings, stabilizing the well wall, and protecting the reservoir. However, the bottom of deep and ultra-deep wells faces harsh conditions of high temperature or even ultra-high temperature. The high temperature stability of drilling fluid under high and ultra-high temperature will face huge challenges. Improper regulation is likely to cause complex safety accidents such as well wall instability and drill stuck, which seriously affects the safety of drilling projects. How to effectively reduce the circulation temperature of drilling fluid at the bottom of ultra-deep wells and improve the tolerance of drilling fluid to high temperature or even ultra-high temperature formations is crucial. At present, certain progress has been made in the cooling methods of drilling fluid at home and abroad. The cooling technology of drilling fluid can reduce the temperature of drilling fluid, thereby reducing the impact of high temperature on the performance of drilling fluid. The main cooling methods of drilling fluid include: ground cooling system of drilling fluid, heat-insulating drilling tools and chemical cooling materials for drilling fluid.

[0003] The most studied chemical cooling materials for drilling fluids are mainly phase change materials. Phase change materials usually absorb a large amount of heat in their phase change temperature range, thereby reducing the temperature of the surrounding environment. Among them, solid-liquid phase change materials have a higher latent heat value of phase change, so they are studied intensively. However, solid-liquid phase change materials will change from solid to liquid at their phase change temperature, and their application in drilling fluids will seriously affect the rheological properties of drilling fluids; when the temperature is lower than their solidification point, such phase change materials will solidify and precipitate from the system to form large blocks, which is very dangerous for drilling operations; in addition, current phase change materials usually have low thermal conductivity, and low thermal conductivity will affect their rapid absorption of heat. By using high thermal conductivity materials to wrap phase change materials, phase change microcapsules with phase change materials as core materials and external high thermal conductivity shells (inorganic shells, etc.) can be formed, which can significantly improve the applicability of solid-liquid phase change materials in drilling fluids.

[0004] Patent document CN117701255A discloses a phase change microcapsule for cooling drilling fluid with silicon dioxide as the outer coating layer and two inorganic salts as the phase change core material. The phase change temperature reaches 236°C and the latent heat of phase change is 192J / g. Although the performance is excellent, the thermal conductivity is unknown. Patent document CN115491183A discloses a method for preparing high temperature and high pressure microspheres for active cooling of drilling fluid. The phase change temperature of this material is less than 150°C and the latent heat reaches 236.1J / g; although the latent heat value is high, it cannot be effectively used for cooling ultra-high temperature formation drilling fluid. Patent document CN113249097A discloses a polyacrylate phase change microcapsule and its preparation method, with a melting point of less than 40°C, a phase change enthalpy value of less than 180J / g, and a phase change temperature that is too low. In addition, the microcapsule uses a polymer to coat the phase change material, resulting in a low thermal conductivity. Summary of the invention

[0005] In view of the shortcomings of the prior art, especially the problems of low phase change temperature and low thermal conductivity of the existing phase change materials, the present invention provides a double-shell high thermal conductivity phase change heat storage microcapsule for ultra-deep drilling fluid and a preparation method and application thereof.

[0006] The present invention prepares a double-shell high thermal conductivity phase change heat storage microcapsule through a two-step coating method. The material has a high phase change temperature (173.3-235.1°C). When it is in the phase change temperature range, it will absorb a large amount of heat and play the role of "phase change latent heat". At the same time, it has excellent thermal conductivity and high thermal conductivity. The application of this material in drilling fluid can significantly reduce the tolerance of the drilling fluid to high-temperature formations. When the drilling fluid circulates to the high-temperature well section (phase change microcapsule phase change temperature), it will absorb a large amount of heat transferred from the high-temperature formation to the drilling fluid, preventing the drilling fluid temperature from rising sharply, thereby avoiding the failure of the drilling fluid system and the instability of the well wall, which is very important for safe and efficient drilling.

[0007] In order to achieve the above object, the present invention is implemented by the following technical solutions:

[0008] A method for preparing double-shell high thermal conductivity phase change heat storage microcapsules for ultra-deep drilling fluids comprises the following steps:

[0009] (1) Primary external shell coating

[0010] a. Preparation of phase change microcapsule material 1

[0011] Phase change material 1, polyvinyl pyrrolidone and emulsifier 1 are sequentially added into deionized water to obtain a supersaturated solution of phase change material 1, and the supersaturated solution of phase change material 1 is heated and stirred in a water bath to obtain a water phase; emulsifier 2 is added into cyclohexane and stirred at high speed to obtain an oil phase;

[0012] The aqueous phase is poured into the oil phase for emulsification, and after emulsification, the mixture of tetraethyl silicate and γ-aminopropyltriethoxysilane is added dropwise. After the reaction is completed, the reaction sample is centrifuged and washed to obtain a phase change microcapsule material 1;

[0013] b. Preparation of phase change microcapsule material 2

[0014] The phase change material 1 is replaced by the phase change material 2, and then the phase change microcapsule material 2 is prepared according to the method in step a;

[0015] c. Preparation of phase change microcapsule material 3

[0016] Phase change material 1 and phase change material 2 are mixed and heated to make the two phase change materials miscible to obtain eutectic phase change material 3, phase change material 1 is replaced by eutectic phase change material 3, and then phase change microcapsule material 3 is prepared according to the method in step a;

[0017] (2) Secondary external shell coating:

[0018] Phase change microcapsule material 1, phase change microcapsule material 2 and phase change microcapsule material 3 are mixed to obtain mixed phase change microcapsules as primary capsule particles, emulsifier 3 and mixed phase change microcapsules are sequentially added into deionized water, and then calcium chloride aqueous solution is dropped into the mixture, and the mixture is continuously stirred to form a stable emulsion, the emulsion is heated and stirred in a water bath, sodium carbonate aqueous solution is added dropwise, and the mixture is continuously and slowly stirred, and secondary wrapped phase change material is obtained by suction filtration, washed and dried at room temperature to obtain double-shell high thermal conductivity phase change heat storage microcapsules.

[0019] Preferably according to the present invention, in step a, the phase change material 1 is galactitol and the emulsifier 1 is Tween 80.

[0020] Preferably, according to the present invention, in step a, the mass ratio of phase change material 1, polyvinyl pyrrolidone and emulsifier 1 is (3-4.5): (0.01-0.03): (0.05-0.2), the mass ratio of phase change material 1 to ionized water is (3-4.5): (10-15), the heating temperature is 40-60°C, and the heating stirring time is 20 min.

[0021] Preferably according to the present invention, in step a, the mass volume ratio of emulsifier 2 to cyclohexane is (0.3-0.8):(50-75), unit, g / mL.

[0022] Preferably according to the present invention, in step a, the high-speed stirring speed is 800-1500 r / min, and the stirring time is 10-30 min.

[0023] Preferably according to the present invention, in step a, the water phase is poured into the oil phase and emulsified at 3000 r / min for 10 min under a shear emulsifier.

[0024] Preferably, according to the present invention, in step a, the water bath heating temperature is 40-60° C., the stirring speed is 400-600 r / min, and the stirring is continued for 10 min.

[0025] Preferably according to the present invention, in step a, the mass ratio of the water phase to the oil phase is (10-20):(40-55), and the volume ratio of tetraethyl silicate to γ-aminopropyltriethoxysilane in the mixture of tetraethyl silicate and γ-aminopropyltriethoxysilane is 1:0.5-0.8.

[0026] Preferably, according to the present invention, in step a, the mass volume ratio of the emulsion after emulsification to the mixture of tetraethyl silicate and γ-aminopropyltriethoxysilane is (70-80): (7-9), unit, g / mL, the reaction time is 10-15h, and cyclohexane is used for washing three times.

[0027] Preferably according to the present invention, in step b, the phase change material 2 is inositol.

[0028] Preferably, according to the present invention, in step c, the mass ratio of phase change material 1 and phase change material 2 is 1.0-2.0:1, the heating temperature is 200-220° C., and the heating time is 8-15 min.

[0029] Preferably according to the present invention, in step (2), the mass ratio of phase change microcapsule material 1, phase change microcapsule material 2, and phase change microcapsule material 3 is 1:1:1, emulsifier 3 is sodium dodecylbenzene sulfonate, and the mass ratio of emulsifier 3, mixed phase change microcapsules and deionized water is (0.8-1.5):(20-40):100.

[0030] Preferably, in step (2), the mass fraction of the calcium chloride aqueous solution is 15-25%, the volume ratio of the calcium chloride aqueous solution added to deionized water is (35-50):100, and after the calcium chloride aqueous solution is added, stirring is continued at a speed of 1000 r / min for 60 minutes to form a stable emulsion.

[0031] Preferably, according to the present invention, in step (2), the emulsion is heated and stirred in a water bath at a temperature of 35-45° C. and a stirring speed of 40-60 r / min.

[0032] Preferably, in step (2), the mass fraction of the sodium carbonate aqueous solution is 15-25%, the volume ratio of the added amount of the sodium carbonate aqueous solution to deionized water is (40-60):100, and after adding the sodium carbonate aqueous solution, the mixture is slowly stirred for 4 hours.

[0033] The invention uses two high melting point phase change materials and eutectic compounds of two phase change materials as core materials, and prepares a double-shell high thermal conductivity phase change heat storage microcapsule for ultra-deep drilling fluid through two outer shell coatings.

[0034] A double-shell high thermal conductivity phase change heat storage microcapsule for ultra-deep drilling fluid is prepared by the method.

[0035] The application of the above-mentioned double-shell high thermal conductivity phase change heat storage microcapsules for ultra-deep drilling fluid is used in oil industry drilling operations and is suitable for cooling ultra-deep well drilling fluid. When the bottom hole temperature is in the phase change temperature range of the phase change heat storage microcapsules, a large amount of heat from the formation is absorbed to reduce the temperature of the circulating drilling fluid. The added amount of the phase change heat storage microcapsules is 4%-8% of the weight of the drilling fluid.

[0036] Through the above technical solution, the beneficial effects of the present invention are:

[0037] 1. The present invention prepares a double-shell high thermal conductivity phase change heat storage microcapsule for drilling fluid through a two-step coating method. The material has a high phase change temperature between 173.3-235.1°C and a phase change enthalpy of up to 211.4 J / g. When it is in the phase change temperature range, it will absorb a large amount of heat and play a role of "phase change latent heat". Applying this material to drilling fluid can significantly reduce the temperature of the drilling fluid and improve the tolerance of the drilling fluid to high-temperature formations.

[0038] 2. The double-shell high thermal conductivity phase change heat storage microcapsules for drilling fluid of the present invention have excellent thermal conductivity, and the thermal conductivity coefficient reaches 2.14W·m -1 ·K -1 , applied to drilling fluid, when the material is at its phase change temperature, it can quickly transfer the heat transferred from the formation to the drilling fluid to the phase change microcapsule and quickly absorb the heat.

[0039] 3. The double-shell high thermal conductivity phase change heat storage microcapsules for drilling fluid of the present invention have excellent temperature resistance. After aging at 220° C. for 16 hours, the high-temperature leakage rate of the phase change microcapsules is only 2.25%. DETAILED DESCRIPTION

[0040] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and understandable, the following is a detailed description of the specific embodiments of the present invention. In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific implementation disclosed below.

[0041] Example 1

[0042] The preparation method of double-shell high thermal conductivity phase change heat storage microcapsules for ultra-deep drilling fluids comprises the following steps:

[0043] (1) Primary external shell coating

[0044] a. Preparation of phase change microcapsule material 1

[0045] Weigh 12g of deionized water, add 3.5g of phase change material 1 galactitol, 0.015g of polyvinyl pyrrolidone, and 0.15g of Tween 80 thereto, prepare a supersaturated solution of phase change material 1 (at room temperature), heat and stir in a water bath at 50°C for 20min to promote the dissolution of phase change material 1, and obtain an aqueous phase; measure 60mL of cyclohexane and place it in a beaker, add 0.6g of Span 80 thereto, and stir at high speed for 20min to obtain an oil phase; pour the aqueous phase into the oil phase and shear the emulsion. The mixture was emulsified at 3000 r / min for 10 min under the presence of a catalytic agent to obtain a stable W / O emulsion, which was heated and stirred at 50°C in a water bath at a stirring speed of 500 r / min for 10 min. Subsequently, 8 mL of tetraethyl silicate and γ-aminopropyltriethoxysilane were measured at a volume ratio of 3:1 and added dropwise to the emulsion using a constant pressure funnel. The reaction was continued for 12 h. Finally, the reaction sample was centrifuged and washed three times with cyclohexane to obtain phase change microcapsules 1.

[0046] b. Preparation of phase change microcapsule material 2

[0047] The phase change material 1 is replaced with the phase change material 2 inositol, and then the phase change microcapsule material 2 is prepared according to the method in step a;

[0048] c. Preparation of phase change microcapsule material 3

[0049] Weigh 4 g of phase change material 1 galactitol and phase change material 2 inositol in a mass ratio of 1.5:1, place in a small crucible and heat at 210° C. for 10 min to dissolve the two phase change materials together to obtain eutectic phase change material 3, and then prepare phase change microcapsule material 3 according to the method in step a;

[0050] (2) Secondary external shell coating:

[0051] Add 100mL of deionized water to a three-necked beaker, and add 1.0g of sodium dodecylbenzene sulfonate, 30g of phase change microcapsules 1, 2 and 3 in a mass ratio of 1:1:1 as primary capsule particles; add 45mL of 20% (mass fraction) calcium chloride aqueous solution dropwise to the system using a constant pressure funnel, and stir continuously for 60min at a speed of 1000r / min to form a stable emulsion; finally, transfer the three-necked flask to a water bath and heat at 40℃ with a stirring speed of 50r / min, add 30mL of 20% (mass fraction) sodium carbonate aqueous solution dropwise to the system using a constant pressure funnel, stir slowly for 4h, and filter to obtain a secondary encapsulated phase change material. The collected product is washed several times with ethanol and deionized water, and then dried at room temperature to obtain a double-shell high thermal conductivity phase change heat storage microcapsule.

[0052] Example 2

[0053] The preparation method of double-shell high thermal conductivity phase change heat storage microcapsules for ultra-deep drilling fluids comprises the following steps:

[0054] (1) Primary external shell coating

[0055] a. Preparation of phase change microcapsule material 1

[0056] Weigh 12g of deionized water, add 3.5g of phase change material 1 galactitol, 0.015g of polyvinyl pyrrolidone, and 0.15g of Tween 80 to it, prepare a supersaturated solution of phase change material 1 (at room temperature), heat and stir in a water bath at 50°C for 20min to promote the dissolution of phase change material 1, and obtain an aqueous phase. Measure 60mL of cyclohexane and place it in a beaker, add 0.6g of Span 80 to it, and stir at high speed for 20min to obtain an oil phase. The aqueous phase was poured into the oil phase and emulsified at 3000 r / min for 10 min under a shear emulsifier to obtain a stable W / O emulsion, which was heated and stirred at 50°C in a water bath at a stirring speed of 500 r / min for 10 min. Subsequently, 8 mL of tetraethyl silicate and γ-aminopropyltriethoxysilane were measured at a volume ratio of 3:1 and added dropwise to the emulsion using a constant pressure funnel. The reaction was continued for 12 h. Finally, the reaction sample was centrifuged and washed three times with cyclohexane to obtain phase change microcapsules 1.

[0057] b. Preparation of phase change microcapsule material 2

[0058] The phase change material 1 is replaced with the phase change material 2 inositol, and then the phase change microcapsule material 2 is prepared according to the method in step a;

[0059] c. Preparation of phase change microcapsule material 3

[0060] Weigh 4 g of phase change material 1 galactitol and phase change material 2 inositol in a mass ratio of 1:1, place in a small crucible and heat at 210° C. for 10 min to dissolve the two phase change materials together to obtain eutectic phase change material 3, and then prepare phase change microcapsule material 3 according to the method in step a;

[0061] (2) Secondary external shell coating:

[0062] Add 100mL of deionized water to a three-necked beaker, and add 1.0g of sodium dodecylbenzene sulfonate 3, phase change microcapsules 1, phase change microcapsules 2, and phase change microcapsules 3 in a mass ratio of 1:1:1, a total of 30g as primary capsule particles; in addition, add 45mL of 20% (mass fraction) calcium chloride aqueous solution dropwise to the system using a constant pressure funnel, and stir continuously for 60min at a speed of 1000r / min to form a stable emulsion. Finally, transfer the three-necked flask to a water bath and heat it at 40°C, set the stirring speed to 50r / min, and use a constant pressure funnel to add 30mL of 20% (mass fraction) sodium carbonate aqueous solution dropwise to the system, stir slowly for 4h, and filter to obtain a secondary encapsulated phase change material. The collected product is washed several times with ethanol and deionized water, and then dried at room temperature to obtain a double-shell high thermal conductivity phase change heat storage microcapsule.

[0063] Example 3

[0064] The preparation method of double-shell high thermal conductivity phase change heat storage microcapsules for ultra-deep drilling fluids comprises the following steps:

[0065] (1) Primary external shell coating

[0066] a. Preparation of phase change microcapsule material 1

[0067] Weigh 12g of deionized water, add 3.5g of phase change material 1 galactitol, 0.015g of polyvinyl pyrrolidone, and 0.15g of Tween 80 to it, prepare a supersaturated solution of phase change material 1 (at room temperature), heat and stir in a water bath at 50°C for 20min to promote the dissolution of phase change material 1, and obtain an aqueous phase. Measure 60mL of cyclohexane and place it in a beaker, add 0.6g of Span 80 to it, and stir at high speed for 20min to obtain an oil phase. The aqueous phase was poured into the oil phase and emulsified at 3000 r / min for 10 min under a shear emulsifier to obtain a stable W / O emulsion, which was heated and stirred at 50°C in a water bath at a stirring speed of 500 r / min for 10 min. Subsequently, 8 mL of tetraethyl silicate and γ-aminopropyltriethoxysilane were measured at a volume ratio of 3:1 and added dropwise to the emulsion using a constant pressure funnel. The reaction was continued for 12 h. Finally, the reaction sample was centrifuged and washed three times with cyclohexane to obtain phase change microcapsules 1.

[0068] b. Preparation of phase change microcapsule material 2

[0069] The phase change material 1 is replaced with the phase change material 2 inositol, and then the phase change microcapsule material 2 is prepared according to the method in step a;

[0070] c. Preparation of phase change microcapsule material 3

[0071] Weigh 4 g of phase change material 1 galactitol and phase change material 2 inositol in a mass ratio of 2:1, place in a small crucible and heat at 210° C. for 10 min to dissolve the two phase change materials together to obtain eutectic phase change material 3, and then prepare phase change microcapsule material 3 according to the method in step a;

[0072] (2) Secondary external shell coating:

[0073] Add 100mL of deionized water to a three-necked beaker, and add 1.0g of sodium dodecylbenzene sulfonate 3, phase change microcapsules 1, phase change microcapsules 2, and phase change microcapsules 3 in a mass ratio of 1:1:1, a total of 30g as primary capsule particles; in addition, add 45mL of 20% (mass fraction) calcium chloride aqueous solution dropwise to the system using a constant pressure funnel, and stir continuously for 60min at a speed of 1000r / min to form a stable emulsion. Finally, transfer the three-necked flask to a water bath and heat it at 40°C, set the stirring speed to 50r / min, and use a constant pressure funnel to add 30mL of 20% (mass fraction) sodium carbonate aqueous solution dropwise to the system, stir slowly for 4h, and filter to obtain a secondary encapsulated phase change material. The collected product is washed several times with ethanol and deionized water, and then dried at room temperature to obtain a double-shell high thermal conductivity phase change heat storage microcapsule.

[0074] Example 4

[0075] The preparation method of double-shell high thermal conductivity phase change heat storage microcapsules for ultra-deep drilling fluids comprises the following steps:

[0076] (1) Primary external shell coating

[0077] a. Preparation of phase change microcapsule material 1

[0078] Weigh 12g of deionized water, add 3.5g of phase change material 1 galactitol, 0.015g of polyvinyl pyrrolidone, and 0.15g of Tween 80 to it, prepare a supersaturated solution of phase change material 1 (at room temperature), heat and stir in a water bath at 50°C for 20min to promote the dissolution of phase change material 1, and obtain an aqueous phase. Measure 60mL of cyclohexane and place it in a beaker, add 0.6g of Span 80 to it, and stir at high speed for 20min to obtain an oil phase. The aqueous phase was poured into the oil phase and emulsified at 3000 r / min for 10 min under a shear emulsifier to obtain a stable W / O emulsion, which was heated and stirred at 50°C in a water bath at a stirring speed of 500 r / min for 10 min. Subsequently, 8 mL of tetraethyl silicate and γ-aminopropyltriethoxysilane were measured at a volume ratio of 3:1 and added dropwise to the emulsion using a constant pressure funnel. The reaction was continued for 12 h. Finally, the reaction sample was centrifuged and washed three times with cyclohexane to obtain phase change microcapsules 1.

[0079] b. Preparation of phase change microcapsule material 2

[0080] The phase change material 1 is replaced with the phase change material 2 inositol, and then the phase change microcapsule material 2 is prepared according to the method in step a;

[0081] c. Preparation of phase change microcapsule material 3

[0082] Weigh 4 g of phase change material 1 galactitol and phase change material 2 inositol in a mass ratio of 2:1, place in a small crucible and heat at 210° C. for 10 min to dissolve the two phase change materials together to obtain eutectic phase change material 3, and then prepare phase change microcapsule material 3 according to the method in step a;

[0083] (2) Secondary external shell coating:

[0084] Add 100mL of deionized water to a three-necked beaker, and add 1.0g of sodium dodecylbenzene sulfonate 3, phase change microcapsules 1, phase change microcapsules 2, and phase change microcapsules 3 in a mass ratio of 1:1:1, a total of 20g as primary capsule particles; in addition, add 45mL of 20% (mass fraction) calcium chloride aqueous solution dropwise to the system using a constant pressure funnel, and stir continuously for 60min at a speed of 1000r / min to form a stable emulsion. Finally, transfer the three-necked flask to a water bath and heat it at 40°C, set the stirring speed to 50r / min, and use a constant pressure funnel to add 30mL of 20% (mass fraction) sodium carbonate aqueous solution dropwise to the system, stir slowly for 4h, and filter to obtain a secondary encapsulated phase change material. The collected product is washed several times with ethanol and deionized water, and then dried at room temperature to obtain a double-shell high thermal conductivity phase change heat storage microcapsule.

[0085] Example 5

[0086] The preparation method of double-shell high thermal conductivity phase change heat storage microcapsules for ultra-deep drilling fluids comprises the following steps:

[0087] (1) Primary external shell coating

[0088] a. Preparation of phase change microcapsule material 1

[0089] Weigh 12g of deionized water, add 3.5g of phase change material 1 galactitol, 0.015g of polyvinyl pyrrolidone, and 0.15g of Tween 80 to it, prepare a supersaturated solution of phase change material 1 (at room temperature), heat and stir in a water bath at 50°C for 20min to promote the dissolution of phase change material 1, and obtain an aqueous phase. Measure 60mL of cyclohexane and place it in a beaker, add 0.6g of Span 80 to it, and stir at high speed for 20min to obtain an oil phase. The aqueous phase was poured into the oil phase and emulsified at 3000 r / min for 10 min under a shear emulsifier to obtain a stable W / O emulsion, which was heated and stirred at 50°C in a water bath at a stirring speed of 500 r / min for 10 min. Subsequently, 8 mL of tetraethyl silicate and γ-aminopropyltriethoxysilane were measured at a volume ratio of 3:1 and added dropwise to the emulsion using a constant pressure funnel. The reaction was continued for 12 h. Finally, the reaction sample was centrifuged and washed three times with cyclohexane to obtain phase change microcapsules 1.

[0090] b. Preparation of phase change microcapsule material 2

[0091] The phase change material 1 is replaced with the phase change material 2 inositol, and then the phase change microcapsule material 2 is prepared according to the method in step a;

[0092] c. Preparation of phase change microcapsule material 3

[0093] Weigh 4 g of phase change material 1 galactitol and phase change material 2 inositol in a mass ratio of 2:1, place in a small crucible and heat at 210° C. for 10 min to dissolve the two phase change materials together to obtain eutectic phase change material 3, and then prepare phase change microcapsule material 3 according to the method in step a;

[0094] (2) Secondary external shell coating:

[0095] Add 100mL of deionized water to a three-necked beaker, and add 1.0g of sodium dodecylbenzene sulfonate 3, phase change microcapsules 1, phase change microcapsules 2, and phase change microcapsules 3 in a mass ratio of 1:1:1, a total of 40g as primary capsule particles; in addition, add 45mL of 20% (mass fraction) calcium chloride aqueous solution dropwise to the system using a constant pressure funnel, and stir continuously for 60min at a speed of 1000r / min to form a stable emulsion. Finally, transfer the three-necked flask to a water bath and heat it at 40°C, set the stirring speed to 50r / min, and use a constant pressure funnel to add 30mL of 20% (mass fraction) sodium carbonate aqueous solution dropwise to the system, stir slowly for 4h, and filter to obtain a secondary encapsulated phase change material. The collected product is washed several times with ethanol and deionized water, and then dried at room temperature to obtain a double-shell high thermal conductivity phase change heat storage microcapsule.

[0096] Example 6

[0097] The preparation method of double-shell high thermal conductivity phase change heat storage microcapsules for ultra-deep drilling fluids comprises the following steps:

[0098] (1) Primary external shell coating

[0099] a. Preparation of phase change microcapsule material 1

[0100] Weigh 12g of deionized water, add 3.5g of phase change material 1 galactitol, 0.015g of polyvinyl pyrrolidone, and 0.15g of Tween 80 to it, prepare a supersaturated solution of phase change material 1 (at room temperature), heat and stir in a water bath at 50°C for 20min to promote the dissolution of phase change material 1, and obtain an aqueous phase. Measure 60mL of cyclohexane and place it in a beaker, add 0.6g of Span 80 to it, and stir at high speed for 20min to obtain an oil phase. The aqueous phase was poured into the oil phase and emulsified at 3000 r / min for 10 min under a shear emulsifier to obtain a stable W / O emulsion, which was heated and stirred at 50°C in a water bath at a stirring speed of 500 r / min for 10 min. Subsequently, 6 mL of tetraethyl silicate and 1 mL of γ-aminopropyltriethoxysilane were added dropwise to the emulsion using a constant pressure funnel, and the reaction was continued for 12 h. Finally, the reaction sample was centrifuged and washed three times with cyclohexane to obtain phase change microcapsules 1.

[0101] b. Preparation of phase change microcapsule material 2

[0102] The phase change material 1 is replaced with the phase change material 2 inositol, and then the phase change microcapsule material 2 is prepared according to the method in step a;

[0103] c. Preparation of phase change microcapsule material 3

[0104] Weigh 4 g of phase change material 1 galactitol and phase change material 2 inositol in a mass ratio of 2:1, place in a small crucible and heat at 210° C. for 10 min to dissolve the two phase change materials together to obtain eutectic phase change material 3, and then prepare phase change microcapsule material 3 according to the method in step a;

[0105] (2) Secondary external shell coating:

[0106] Add 100mL of deionized water to a three-necked beaker, and add 1.0g of sodium dodecylbenzene sulfonate 3, phase change microcapsules 1, phase change microcapsules 2, and phase change microcapsules 3 in a mass ratio of 1:1:1, a total of 30g as primary capsule particles; in addition, add 45mL of 20% (mass fraction) calcium chloride aqueous solution dropwise to the system using a constant pressure funnel, and stir continuously for 60min at a speed of 1000r / min to form a stable emulsion. Finally, transfer the three-necked flask to a water bath and heat it at 40°C, set the stirring speed to 50r / min, and use a constant pressure funnel to add 30mL of 20% (mass fraction) sodium carbonate aqueous solution dropwise to the system, stir slowly for 4h, and filter to obtain a secondary encapsulated phase change material. The collected product is washed several times with ethanol and deionized water, and then dried at room temperature to obtain a double-shell high thermal conductivity phase change heat storage microcapsule.

[0107] Comparative Example 1

[0108] The preparation method as described in Example 1, except that:

[0109] Phase change microcapsules 1 are not added in step (2).

[0110] Comparative Example 2

[0111] The preparation method as described in Example 1, except that:

[0112] Phase change microcapsules 2 are not added in step (2).

[0113] Comparative Example 3

[0114] The preparation method as described in Example 1, except that:

[0115] Phase change microcapsules 3 are not added in step (2).

[0116] Comparative Example 4

[0117] The preparation method as described in Example 1, except that:

[0118] Step (2), 30 g of phase change microcapsule 1, phase change microcapsule 2 and phase change microcapsule 3 in a mass ratio of 1:1:1 are mixed without secondary shell coating.

[0119] Comparative Example 5

[0120] The preparation method as described in Example 1, except that:

[0121] Step c, weigh 4 g of phase change material 1 galactitol and phase change material 2 inositol in a mass ratio of 1.5:1 and directly mix them without high-temperature miscibility operation of the two phase change materials; obtain eutectic phase change material 3, and then prepare phase change microcapsule material 3 according to the method in step a.

[0122] Experimental example

[0123] The high thermal conductivity double-shell phase change heat storage microcapsules prepared in the examples and comparative examples were evaluated as follows: phase change temperature and phase change latent heat analysis, thermal conductivity, high temperature leakage rate, and particle size distribution.

[0124] (1) Phase change temperature and phase change latent heat analysis

[0125] The selection of phase change materials in engineering applications is based on two principles, namely, having a suitable phase change temperature and a phase change latent heat value. In ultra-deep drilling, suitable phase change materials have an important influence on effectively reducing the temperature of the bottom hole circulating drilling fluid. Therefore, this section determines the phase change temperature and phase change enthalpy of each embodiment and comparative sample. The specific operation method is: the German-Netsch-DSC214 differential scanning calorimeter is used to measure the phase change temperature and phase change enthalpy of each embodiment and comparative cooling material. The test conditions are: temperature range 40℃-300℃, heating rate 5K·min-1, nitrogen is selected as the protective gas, and the gas flow rate is 20.0mL·min-1. The experimental results are shown in Table 1.

[0126] Table 1 Phase change temperature and phase change latent heat results

[0127]

[0128] Table 1 shows the phase change temperature and phase change enthalpy of each embodiment and comparative sample. As can be seen from Table 1, embodiment 1 shows the best phase change temperature range and phase change enthalpy, the phase change temperature is between 173.3-230.7℃, and the phase change enthalpy is as high as 211.4J / g. Comparative Examples 1, 2, and 3 do not add phase change microcapsules 1, 2, and 3 respectively, which have a significant effect on the phase change temperature and latent heat of phase change. Two temperature sections appear in the phase change temperature range, and the phase change enthalpy is significantly reduced; Comparative Example 4 does not carry out secondary shell coating, although it has no significant effect on the phase change temperature, but the phase change enthalpy is reduced. In comparative example 5, when preparing phase change microcapsule material 3, the two phase change materials are not mixed at high temperature, and no eutectic compound is produced, so the final phase change material phase change temperature range has two discontinuous phase change temperature stages.

[0129] (2) Thermal conductivity measurement

[0130] 100 g of each example and comparative example sample were selected, and the thermal conductivity of each example and comparative example sample was measured using a hotdisk thermal conductivity tester. The results are shown in Table 2.

[0131] Table 2 Thermal conductivity measurement results of phase change heat storage microcapsules

[0132]

[0133] The results of thermal conductivity measurements of the samples of each embodiment and comparative example are shown in Table 2. As can be seen from Table 2, the thermal conductivity of embodiment 1 is the highest. In embodiment 6, the amount of KH550 added is reduced, resulting in a weakened hydrolysis performance of tetraethyl silicate, which affects the coating of the primary phase change microcapsules, resulting in a decrease in thermal conductivity compared to embodiment 1. In comparative examples 1, 2 and 3, respectively, the absence of phase change microcapsules 1, 2 and 3 has a significant impact on the overall thermal conductivity of the material, and the thermal conductivity is significantly reduced. In comparative example 4, the secondary shell coating operation is not performed, and the overall thermal conductivity of the material is weakened. This is because the secondary coated inorganic calcium carbonate shell can well improve the thermal conductivity of the phase change heat storage microcapsule material. In the preparation process of comparative example 5, high-temperature miscibility was not performed during the preparation of phase change microcapsules 3, which had no effect on the overall thermal conductivity of the material.

[0134] (3) High temperature leakage rate measurement

[0135] The two phase change materials selected in the present invention are galactitol and inositol, which are two typical solid-liquid phase change heat storage materials. When the phase change material is applied to the drilling fluid, when it is in its phase change temperature range, the phase change material changes from solid to liquid, which will seriously affect the rheological stability of the drilling fluid at high temperature. The present invention reduces the influence of its phase change after high-temperature phase change on the rheological properties of the drilling fluid by coating the phase change material with an external shell.

[0136] The main operating steps of the high-temperature leakage rate experiment are as follows: add 12g of the example or comparative example sample to 400mL and stir at a low speed for 20min until the sample is fully dispersed in the aqueous phase to obtain an example or comparative example aqueous solution with a mass fraction of 3%. After the preparation, add each sample solution to an aging tank and age at 220°C for 16h. After the aging is completed, centrifuge the solid phase in the solution and dry it at 80°C to constant weight and record its mass as M. Calculate the high-temperature leakage rate as shown in formula (1.1). The experimental results are shown in

[0137] As shown in Table 3.

[0138]

[0139] Where: R is the high temperature leakage rate, %;

[0140] M is the mass of the sample after centrifugation and drying, g.

[0141] Table 3 Results of high temperature leakage rate of phase change heat storage microcapsules

[0142] sample High temperature leakage rate (%) sample High temperature leakage rate (%) Example 1 2.25 Comparative Example 1 2.38 Example 2 2.14 Comparative Example 2 2.21 Example 3 2.34 Comparative Example 3 2.14 Example 4 2.10 Comparative Example 4 10.56 Example 5 2.76 Comparative Example 5 2.23 Example 6 3.12

[0143] The experimental results of high temperature leakage rate of each embodiment and comparative example are shown in Table 3. As can be seen from Table 3, comparative examples 1, 2, and 3 do not add phase change microcapsules 1, 2, and 3, respectively, which have a certain impact on the high temperature leakage rate of the phase change heat storage microcapsules, but the overall impact is small. The operation of comparative example 4 affects the coating of the primary shell layer and the coating of the secondary shell layer, respectively, and therefore has a greater impact on the high temperature leakage rate of the phase change heat storage microcapsules finally prepared. In the process of material preparation of comparative example 5, phase change microcapsules 3 are not mixed at high temperature during preparation, which has a certain impact on the high temperature leakage rate of the phase change heat storage microcapsules, but the overall impact is small.

[0144] (4) Particle size distribution test

[0145] The selected embodiment is to prepare a sample solution with a mass fraction of 3% by mass, stir for 20 minutes, ultrasonically disperse for 20 minutes, and use Malvern 3000 particle size analyzer to measure the particle size distribution of each sample. Subsequently, the above materials are placed in an aging tank and aged at 220°C for 16 hours, and the particle size test is performed again. The experimental results are shown in Table 4.

[0146] Table 4 Particle size distribution of phase change heat storage microcapsules

[0147]

[0148]

[0149] The particle size distribution of each embodiment and comparative example sample in water is shown in Table 4. As can be seen from Table 4, comparative example 4 does not perform secondary shell coating, so the particle size is reduced. Compared with embodiment 1, the particle size of other embodiments and comparative examples does not change much, indicating that the factors in these examples have a basically negligible effect on the particle size of the final phase change heat storage microcapsules.

[0150] Through comprehensive evaluation of the above four experiments, it is concluded that the sample of Example 1 has the best "thermal conductivity", "temperature resistance", "high latent heat" and "low leakage", and has excellent comprehensive performance.

Claims

1. A method for preparing double-shell high thermal conductivity phase change heat storage microcapsules for ultra-deep drilling fluid, comprising the following steps: (1) Primary external shell coating a. Preparation of phase change microcapsule material 1 Phase change material 1, polyvinyl pyrrolidone and emulsifier 1 are sequentially added into deionized water to obtain a supersaturated solution of phase change material 1, and the supersaturated solution of phase change material 1 is heated and stirred in a water bath to obtain a water phase; emulsifier 2 is added into cyclohexane and stirred at high speed to obtain an oil phase; The aqueous phase is poured into the oil phase for emulsification, and after emulsification, the mixture of tetraethyl silicate and γ-aminopropyltriethoxysilane is added dropwise. After the reaction is completed, the reaction sample is centrifuged and washed to obtain a phase change microcapsule material 1; b. Preparation of phase change microcapsule material 2 The phase change material 1 is replaced by the phase change material 2, and then the phase change microcapsule material 2 is prepared according to the method in step a; c. Preparation of phase change microcapsule material 3 Phase change material 1 and phase change material 2 are mixed and heated to make the two phase change materials miscible to obtain eutectic phase change material 3, phase change material 1 is replaced by eutectic phase change material 3, and then phase change microcapsule material 3 is prepared according to the method in step a; (2) Secondary external shell coating: Phase change microcapsule material 1, phase change microcapsule material 2 and phase change microcapsule material 3 are mixed to obtain mixed phase change microcapsules as primary capsule particles, emulsifier 3 and mixed phase change microcapsules are sequentially added into deionized water, and then calcium chloride aqueous solution is dropped into the mixture, and the mixture is continuously stirred to form a stable emulsion, the emulsion is heated and stirred in a water bath, sodium carbonate aqueous solution is added dropwise, and the mixture is continuously and slowly stirred, and secondary wrapped phase change material is obtained by suction filtration, washed and dried at room temperature to obtain double-shell high thermal conductivity phase change heat storage microcapsules.

2. The preparation method according to claim 1, characterized in that: In step a, the phase change material 1 is galactitol, the emulsifier 1 is Tween 80, the mass ratio of the phase change material 1, polyvinyl pyrrolidone and emulsifier 1 is (3-4.5): (0.01-0.03): (0.05-0.2), the mass ratio of the phase change material 1 to the ionized water is (3-4.5): (10-15), the heating temperature is 40-60°C, and the heating stirring time is 20 minutes.

3. The preparation method according to claim 1, characterized in that: In step a, the mass volume ratio of emulsifier 2 to cyclohexane is (0.3-0.8):(50-75), unit, g / mL.

4. The preparation method according to claim 1, characterized in that: In step a, the high-speed stirring speed is 800-1500r / min, the stirring time is 10-30min, the water phase is poured into the oil phase and emulsified at 3000r / min for 10min under shear emulsifier, the water bath heating temperature is 40-60°C, the stirring speed is 400-600r / min, and the stirring is continued for 10min.

5. The preparation method according to claim 1, characterized in that: In step a, the mass ratio of the aqueous phase to the oil phase is (10-20): (40-55), the volume ratio of tetraethyl silicate to γ-aminopropyl triethoxysilane in the mixture of tetraethyl silicate and γ-aminopropyl triethoxysilane is 1:0.5-0.8, the mass volume ratio of the emulsion after emulsification to the mixture of tetraethyl silicate and γ-aminopropyl triethoxysilane is (70-80): (7-9), unit, g / mL, the reaction time is 10-15h, and cyclohexane is used for washing three times.

6. The preparation method according to claim 1, characterized in that: In step b, phase change material 2 is inositol, and in step c, the mass ratio of phase change material 1 and phase change material 2 is 1.0-2.0:1, the heating temperature is 200-220° C., and the heating time is 8-15 min.

7. The preparation method according to claim 1, characterized in that: In step (2), the mass ratio of phase change microcapsule material 1, phase change microcapsule material 2, and phase change microcapsule material 3 is 1:1:1, emulsifier 3 is sodium dodecylbenzene sulfonate, the mass ratio of emulsifier 3, mixed phase change microcapsules and deionized water is (0.8-1.5): (20-40): 100, the mass fraction of calcium chloride aqueous solution is 15-25%, and the volume ratio of the added amount of calcium chloride aqueous solution to deionized water is (35-50):

100. After adding the calcium chloride aqueous solution, stirring is continued at a speed of 1000r / min for 60min to form a stable emulsion.

8. The preparation method according to claim 1, characterized in that: In step (2), the emulsion is heated and stirred in a water bath at a temperature of 35-45° C., a stirring speed of 40-60 r / min, a mass fraction of the sodium carbonate aqueous solution is 15-25%, and a volume ratio of the added amount of the sodium carbonate aqueous solution to deionized water is (40-60):

100. After adding the sodium carbonate aqueous solution, the mixture is slowly stirred for 4 hours.

9. A double-shell high thermal conductivity phase change heat storage microcapsule for ultra-deep drilling fluid, prepared by the method according to any one of claims 1 to 8.

10. The application of the double-shell high thermal conductivity phase change heat storage microcapsules for ultra-deep drilling fluids as claimed in claim 9 is used in drilling operations in the petroleum industry and is suitable for cooling ultra-deep well drilling fluids. When the bottom hole temperature is within the phase change temperature range of the phase change heat storage microcapsules, a large amount of heat from the formation is absorbed to reduce the temperature of the circulating drilling fluid. The addition amount of the phase change heat storage microcapsules is 4%-8% of the weight of the drilling fluid.

Citation Information

Patent Citations

  • Polyacrylate phase change microcapsules and preparation method thereof

    CN113249097A

  • Preparation method and application of high-temperature-resistant high-pressure-resistant microspheres for active cooling of high-temperature drilling fluid

    CN115491183A

  • Phase change heat storage microcapsule material suitable for cooling drilling fluid and preparation method of phase change heat storage microcapsule material

    CN116063996A

  • Phase change microcapsule, preparation method thereof and water-based drilling fluid

    CN117070198A

  • Phase change capsule for cooling drilling fluid as well as preparation method and application of phase change capsule

    CN117701255A

Cited By

  • Silicon dioxide-polyurethane composite phase change microcapsule for water-based drilling fluid as well as preparation method and application of silicon dioxide-polyurethane composite phase change microcapsule

    CN122255950A